ONLINE COLLABORATIVE LANGUAGE LEARNING FOR IMPROVING EFL STUDENTS’ WRITING SKILLS - Sevara Davronova Ulug‘bekovna PhD student, teacher at English and Literature Department, Gulistan State University, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This thesis examines the impact of online collaborative learning on EFL (English as a Foreign Language) students' writing skills. It highlights the benefits of peer feedback, authentic writing practice, and the development of critical thinking through collaborative tasks. The findings show that online collaboration enhances students' writing abilities by facilitating constructive feedback, encouraging writing for real audiences, and promoting deeper learning through diverse perspectives. The study concludes that integrating these strategies into language teaching can significantly improve students' writing skills and overall language proficiency, preparing them for real-world communication. Future research should optimize these strategies and address implementation challenges.